Platelets: bridging hemostasis, inflammation, and immunity. Issue 3 (17th April 2013) - Jenne, C. N.; Urrutia, R.; Kubes, P.
Summary Although the function of platelets in the maintenance of hemostasis has been studied in great detail, more recent evidence has highlighted a central role for platelets in the host inflammatory and immune responses. Platelets by virtue of their large numbers and their ability to rapidly release a broad spectrum of immunomodulatory cytokines, chemokines, and other mediators act as circulating sentinels. Upon detection of a pathogen, platelets quickly activate and begin to drive the ensuing inflammatory response. Platelets have the ability to directly modulate the activity of neutrophils (phagocytosis, oxidative burst), endothelium (adhesion molecule and chemokine expression), and lymphocytes. Due to their diverse array of adhesion molecules and preformed chemokines, platelets are able to adhere to leukocytes and facilitate their recruitment to sites of tissue damage or infection. Furthermore, platelets directly participate in the capture and sequestration of pathogens within the vasculature. Platelet–neutrophil interactions are known to induce the release of neutrophil extracellular traps (NETs) in response to either bacterial or viral infection, and platelets have been shown to internalize pathogens, sequestering them in engulfment vacuoles. Finally, emerging data indicate that platelets also participate in the host immune response by directly killing infected cells. This review will highlight the central role platelets play in the initiation and modulation of the host inflammatory and immune responses.